Chromosome-level genome assembly and population genomic resource to accelerate orphan crop lablab breeding - Njaci, Isaac; Waweru, Bernice; Kamal, N.; Muktar, Meki S.; Fisher, D.; Gundlach, H.; Muli, Collins; Muthui, Lucy; Maranga, M.; Kiambi, D.; Maass, Brigitte L.; Emmrich, P.M.F.; et al. (Springer, 2023)
Under-utilised orphan crops hold the key to diversified and climate-resilient food systems. Here, we report on orphan crop genomics using the case of Lablab purpureus (L.) Sweet (lablab) - a legume native to Africa and cultivated throughout the tropics for food and forage. Our Africa-led plant genome collaboration produces a high-quality chromosome-scale assembly of the lablab genome. Our assembly highlights the genome organisation of the trypsin inhibitor genes - an important anti-nutritional factor in lablab. We also re-sequence cultivated and wild lablab accessions from Africa confirming two domestication events. Finally, we examine the genetic and phenotypic diversity in a comprehensive lablab germplasm collection and identify genomic loci underlying variation of important agronomic traits in lablab. The genomic data generated here provide a valuable resource for lablab improvement. Our inclusive collaborative approach also presents an example that can be explored by other researchers sequencing indigenous crops, particularly from low and middle-income countries (LMIC).